Monetary policy, ownership structure, and risk-taking at financial intermediaries - Caselli, Giorgio; Figueira, Catarina (Wiley, 2023)
This paper examines how ownership structure interacts with monetary policy in shaping financial intermediaries' appetite for risk. By constructing a large panel of banks across Western Europe, we provide evidence that differences in bank ownership influence the transmission of monetary policy via the risk-taking channel. While shareholder banks actively adjust the riskiness of their portfolios to changes in interest rates, stakeholder banks appear to be less responsive to such changes. These findings call for greater attention to the nature of bank ownership when setting monetary policy.
Keywords: bank ownership; financial crisis; macroprudential policy; monetary transmission mechanism; risk-taking channel; systemic risk